Comparison of Wear Resistance, Surface Hardness and Surface Roughness of Dentoform Tooth and Silane-treated Alumina Reinforced Epoxy Resin - Arwatchanakan, Sukontip; Thanaphumphong, Nawiya; Suwanprateeb, Jintamai; Arksornnukit, Mansuang (Khon Kaen University Dental Journal, 2020)
Dentoform teeth are extensively used in the preclinical laboratory practice by dental students. Nowadays, the price of the dentoform teeth has been increased continuously. Therefore, the substitute materials were developed in order to reduce the imported teeth thus reducing the education expenses for dental students. The purpose of this study were to compare wear resistance, surface hardness and surface roughness of dentoform teeth (Frasaco, German; Nissin, Japan) and epoxy composite (70 wt% un-treated alumina and 50, 60, 70 wt% silane-treated alumina reinforced epoxy resin) when unfilled epoxy resin served as control. Fifteen specimens of each group (n=15) were examined for pin-on-disk wear resistance, Vickers surface hardness and contact stylus profilometer surface roughness. One-Way ANOVA statistic was used to analyze the data (a = 0.05). It was found that wear resistance of 70 wt% and 60 wt% silane-treated alumina reinforced epoxy resin groups (tx 70% and tx 60% groups) were significantly higher than those of the others including dentoform groups. The surface hardness of dentoform groups was significant higher than all remaining groups (Frasaco: 38.321+1.278 HV, Nissin: 39.245+2.060 HV). However, when comparing within the epoxy composite groups, tx 70% group (29.924+0.921) had been shown the significantly highest value. In surface roughness, tx 60% group had been revealed the lowest value but it was not significantly different with tx 50% and tx 70% groups. Although tx 70% group had been shown less surface hardness when compared with that of dentoform groups, its wear resistance and surface roughness had been superior than those of dentoform groups. Therefore, tx 70% should be considered as a promising and cost-effective substitute material for production of dentoform teeth.